In Situ Electrostimulation Drives a Regenerative Shift in the Zone of Infarcted Myocardium. Issue 3 (March 2013) - Spadaccio, Cristiano; Rainer, Alberto; De Marco, Federico; Lusini, Mario; Gallo, Paolo; Sedati, Pietro; Muda, Andrea Onetti; De Porcellinis, Stefano; Gregorj, Chiara; Avvisati, Giuseppe; Trombetta, Marcella; Chello, Massimo; et al.
Electrostimulation represents a well-known trophic factor for different tissues. In vitro electrostimulation of non-stem and stem cells induces myogenic predifferentiation and may be a powerful tool to generate cells with the capacity to respond to local areas of injury. We evaluated the effects of in vivo electrostimulation on infarcted myocardium using a miniaturized multiparameter implantable stimulator in rats. Parameters of electrostimulation were organized to avoid a direct driving or pacing of native heart rhythm. Electrical stimuli were delivered for 14 days across the scar site. In situ electrostimulation used as a cell-free, cytokine-free stimulation system, improved myocardial function, and increased angiogenesis through endothelial progenitor cell migration and production of vascular endothelial growth factor (VEGF). In situ electrostimulation represents a novel means to stimulate repair of the heart and other organs, as well as to precondition tissues for treatment with cell-based therapies.